Wybrane zagadnienia zarządzania jakością w małym zakładzie przetwórstwa mięsnego - Chądrzyński, Mariusz (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2001)
The paper discusses some problems connected with quality management in meat processing plant of small size. The author placed emphasis on the following: some theoretical aspects of quality systems particularly applied in food industry; identified benefits and difficulties connected with the applying quality systems in practice; illustrative quality-oriented activities in small plants of meat processing; planned quality-oriented activities in the investigated plant; the situation of the plant under the process of HACCP system implementation.